2020
DOI: 10.3390/md18090462
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Effect of Pentadecapeptide Derived from Cyclina sinensis on Cyclophosphamide-Induced Nephrotoxicity

Abstract: Cyclophosphamide (CTX) is a widely used anticancer drug with severe nephrotoxicity. The pentadecapeptide (RVAPEEHPVEGRYLV) from Cyclina sinensis (SCSP) has been shown to affect immunity and to protect the liver. Hence, the purpose of this study was to investigate the ameliorating effect of SCSP on CTX-induced nephrotoxicity in mice. We injected male ICR mice with CTX (80 mg/kg·day) and measured the nephrotoxicity indices, levels of antioxidant enzymes, malondialdehyde (MDA), inflammatory factors, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…[23 -25] Indeed, numerous reports have shown that CTX depleted antioxidant enzymes (SOD, GSH, CAT and GPx), increased ROS and lipid peroxidation in the kidney, testes, liver and bladder of CTX exposed animals. [10,23,26] Likewise, the results obtained from this study indicated renal oxidative damage in the CTX treated animals as evident by significant declines in renal activities of SOD, CAT, GSH and GPx, while MDA content was increased. SRPF displayed significant antioxidant activity via restoration of renal antioxidant capacities (elevated SOD, CAT, GPx and GSH activities as well as decreased MDA level).…”
Section: Discussionsupporting
confidence: 63%
“…[23 -25] Indeed, numerous reports have shown that CTX depleted antioxidant enzymes (SOD, GSH, CAT and GPx), increased ROS and lipid peroxidation in the kidney, testes, liver and bladder of CTX exposed animals. [10,23,26] Likewise, the results obtained from this study indicated renal oxidative damage in the CTX treated animals as evident by significant declines in renal activities of SOD, CAT, GSH and GPx, while MDA content was increased. SRPF displayed significant antioxidant activity via restoration of renal antioxidant capacities (elevated SOD, CAT, GPx and GSH activities as well as decreased MDA level).…”
Section: Discussionsupporting
confidence: 63%
“…Research has revealed that CYP treatment promoted the level of apoptotic protein in mice (Jiang et al. 2020 ). To evaluate the anti-apoptotic role of HQH in CYP-treated rats, we determined the expression of caspase-3, caspase-9, and the ratio of the pro-apoptotic protein Bax to the anti-apoptotic protein Bcl-2 by western blot ting analysis ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…8,9 CTX, as an inactive prodrug, enters into the human body and forms the unstable 4-hydroxycyclophosphamide through the metabolic transformation of the cytochrome P450 (CYP450) enzyme, then generates phosphoramide mustard and acrolein. [10][11][12] Phosphoramide mustard is an effective metabolite of CTX, which kills cancer cells. It can alkalize cellular nucleic acids and inhibit the proliferation and division of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclophosphamide (CTX) is a popular broad‐spectrum anticancer agent used in clinical practice 8,9 . CTX, as an inactive prodrug, enters into the human body and forms the unstable 4‐hydroxycyclophosphamide through the metabolic transformation of the cytochrome P450 (CYP450) enzyme, then generates phosphoramide mustard and acrolein 10‐12 . Phosphoramide mustard is an effective metabolite of CTX, which kills cancer cells.…”
Section: Introductionmentioning
confidence: 99%